Noise levels and hearing impairment in an urban community in Ibadan, Southwest Nigeria (2008)
Aim The study sought to measure the noise levels in an urban community and assess the hearing levels of persons working within the community. Subjects and methods Noise levels were measured in selected locations in Ibadan, southwest Nigeria, using a sound level meter CEL 269 (CEL Instruments UK Ltd.). Measurements were done between the hours of 08:00 and 15:00. Audiometric screening was done on 51 persons working within the community to determine the occurrence of hearing impairment. Results The noisiest locations were workshops using machines such as saw mills, 95–102 dBA; carpentry tools, 87–101 dBA; printing presses, 85–88 dBA; and grain mills, 88–105 dBA. Music shops also constituted a nuisance with noise levels of 89–99 dBA. Roadside noise levels on major road junctions were 86–90 dBA and 61–65 dBA on side streets. Noise levels in designated markets ranged from 65– 69 dBA and 61–81 dBA in street markets. Within residential areas, noise levels ranged from 39–41 dBA in low-density areas to 55–59 dBA in high-density areas. Audiometric screening showed that 28 participants (55%) had normal hearing. Mild and moderate hearing impairment was recorded among 17(33%) and 6 (11.7%) participants, respectively. Of the 23 who were hearing impaired, 10 had bilateral impairment. The prevalence of hearing impairment increased with age from 14% in the 2nd decade to 75% in the 5th decade. Conclusion Noise levels in several areas of the city exceed WHO guideline values and constitute a public health hazard to residents and street workers. There is a need for regulation and control of the social and economic activities that generate noise. This may reduce the occurrence of hearing impairment and other adverse health outcomes in the general population.